PERANCANGAN PANTI ASUHAN DENGAN KONSEP ARSITEKTUR RAMAH ANAK - Azkiah, Shofirah; Widati, Titiani; Sanitha, Onie Dian (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Orphanages are social institutions that provide shelter for orphans and abandoned children due to family dysfunction. In Indonesia, most orphanages are managed by communities, resulting in varying quality of physical environments. A case study at Ayah Bunda Orphanage in Palangka Raya reveals issues such as low social interaction and high levels of loneliness among children. These conditions are worsened by conventional building designs with minimal spaces for play, interaction, and shared learning. A monotonous and enclosed environment hinders children's social and emotional development. This research aims to design a new orphanage complex using a child-friendly architectural approach that integrates principles of safety, comfort, accessibility, creativity stimulation, spatial flexibility, social interaction, and connection with nature. Through a descriptive qualitative method and case study, the design seeks to create a safe, inclusive living environment that supports children’s holistic development. This architectural proposal is expected to serve as a solution to social isolation among orphanage children by offering participatory, open, and engaging spaces.